Geochemistry of sedimentary organic matter and trace elements in modern lake sediments from transitional karstic land-sea environment of the Neretva River delta (Kuti Lake, Croatia). (20th November 2018) - Ivanić, Maja; Lojen, Sonja; Grozić, Dino; Jurina, Irena; Škapin, Srečo D.; Troskot-Čorbić, Tamara; Mikac, Nevenka; Juračić, Mladen; Sondi, Ivan
Abstract: This paper investigates recent sedimentation processes and geochemistry of sedimentary organic matter (SOM) and trace elements in a unique semi-enclosed lacustrine sedimentation system in a transitional land-sea environment of the Neretva River delta. The results have shown that the influence of the Neretva River on the lake sedimentation processes is limited to short-term flood events carrying terrigenous loads, while the authigenic formation of nanostructured calcite is the primary source of sediments in the recent past. The enhanced release of biogenic CO2 into the pore water, deriving from the decomposition of SOM, acts as a major contributor to this process. The occurrence of early formed syngenetic and diagenetic pyrite indicates the existence of oxygen-depleted conditions in the investigated system in the recent past. The input of terrigenous material was identified as the main source of trace elements (Pb, Cu, Zn, Sn) in the lake sediments. The distribution of redox sensitive elements (Mo, Tl, V) particularly depends on the oxygen deficiency and the formation of sedimentary pyrite. The human impact in the study area is negligible, although somewhat elevated concentrations of Sn were found in the surface sediment layers. Finally, the results obtained indicate that the Kuti Lake represents a unique lacustrine environment which can be viewed as an isolated sedimentological and biogeochemical system in the Neretva River delta.